The Communication Barriers between Teachers and Parents in Primary Schools - Ozmen, Fatma; Akuzum, Cemal; Zincirli, Muhammed; Selcuk, Gulenaz (Ani Yayincilik, 2016)
Problem Statement: In educational institutions, the effectiveness of communication between teachers and parents, in terms of student achievement and attendance, has a great importance. Parent-teacher communication provides multi-faceted benefits to teachers, the school, and parents as well. However, various obstacles hinder the realization of effective parent-teacher communication in school settings. Purpose of Study: The main purpose of this study is to determine the communication barriers between parents and teachers, based on the views of primary school teachers. This study is seen as important since it addresses the barriers in communication, which is seen as vital for achieving educational aims effectively. Effective communication provides achievement and improvement by providing support to parents, students, teachers, and schools and promoting appropriate environments. Method: This research is a survey type descriptive study. Due to the stratified and random type sample formation, 850 teachers were considered to be taken into the research sample; however, 514 of the distributed questionnaires were found valid. The data collection tool used was a four-dimensioned scale developed by the researchers themselves. In the analysis of the data, parametric and non-parametric tests were used. Findings: The findings revealed that teachers experienced individual barriers at a general level, but other socio-cultural, accessibility, and field and status related barriers at were experienced at the very rare level without any significant differences considering the gender and branches of the teachers. However, novice teachers (5 years and less work experience) stated significantly the most individual barriers and the most barriers related to the other dimensions as well. Results and Suggestions: The results obtained in this study show the same major communication preventive issues between teachers and parents documented in the literature. Thus, results such as physical distance, socio-cultural differences (language, dress, values), meeting with parents only when money is required, parents' lack of trust in teachers and their unwillingness for cooperation, parents' financial problems and lack of interest about informing parents of school-related issues, inappropriate schedule of school activities, teachers' misbehaviors, parents' education level, parents' mistrust in teachers and managers, and the like also confirm the situation represented in previous research. It was recommended that school managers and teachers adopt an open-door policy for parents; and the schools should take the initiative of realizing collaborative efforts among the school staff, parents, and other relevant institutions in order to eliminate communication barriers. The training of the school administrators, teachers, and families about gaining effective communication skills that will contribute to student achievement should be emphasized.
İlköğretim okullarında öğretmen-veli iletişiminde karşılaşılan engeller
Keywords: Schools; teachers; parents; effective communication; communication barriers